Protein-Solvent Interaction of Thermostable Lipase for Biocatalysis in Organic Solvents - Tengku Abdul Hamid, Tengku Haziyamin (2009)
A high expression of a solvent stable enzyme enables characterization of it solvent stability profiles which could aid in many aspects of structural studies in understanding protein-solvent interaction. A thermostable and solvent stable lipase (Lip 42) gene previously isolated from Bacillus sp. strain 42 was subcloned into pET-51b. High expression was achieved using this vector which employs T7 promoter, using E. coli host strain BL21(DE3)pLysS. Expression was achieved at 160 U/mg protein, after 25 hour incubation at 37°C using 0.5 mM isopropyl β-d-thiogalactopyranoside (IPTG). Lip 42 was purified using Strep-tag affinity chromatography and it molecular weight size is 43 kDa by SDS-PAGE. Studies on purified lipase in solvent with different polarities (log P values) showed that it was generally stable in water miscible solvents such as DMSO, DMF, ethanol, and methanol; and in apolar solvent such as n-hexane. The enzyme retained high residual activities in 45 to 60% v/v hydrophilic solvents, and also some enhancements (> 100%) were observed in low DMSO compositions (15-30% v/v). Stability preference in water miscible solvents would make Lip 42 lipase a suitable enzyme to be employed in bio-diesel production. Structural characterizations of the enzyme in different solvent compositions were carried out using fluorescence spectroscopy, and also by using both far- and near- UV circular dichroisms (CD). Both secondary and tertiary structures were retained in low solvent (<45% v/v), but in > 60% v/v, the tertiary structure was perturbed accompanied by the formation of molten globule (MG), or an expanded helical structure state. Far-UV CD studies in methanol indicated the conserved secondary structure with an increase in α-helices, and decreased in β-sheets. Near UV-CD spectra in low methanol and DMSO compositions (30 - 45% v/v) resembled the native protein. At solvent > 60% v/v, the distinct tertiary structure perturbation was observed each in methanol and DMSO. Intrinsic fluorescence spectra in both solvents showed blue shifts at 0-45% v/v indicating a buried Tryptophan, and at > 60% v/v showed red shift indicating an exposed Tryptophan. Extrinsic fluorescence studies showed the possible formation of inactive molten globule (MG) at > 60% v/v solvent. In this state, the collapse of tertiary structure with an intact secondary structure was manifested by the loss in biological function. Based on solvent stability profiles, molecular dynamic (MD) simulations were run in the presence of water, 60% v/v DMSO + 40% v/v water, and 100% v/v DMSO.Structural (RMSD) and flexibility (RMSF) changes indicated that the major changes in the lid involving two helix-loop-helix motif loops. In 60% v/v DMSO, the gap between the loops was narrower and there was a collapse of a nearby hydrophobic cluster. However, the cluster was still seen in water and neat (100% v/v) DMSO. Consequently, the H-bond interaction and hydrophobic cluster region are important elements in protein solvent interaction. A site-directed mutation on the lid region (V171S) with residue Ser 171 replacing Val (hydrophobic to polar) impaired the enhancement in low solvent compositions. This effect was more pronounced at higher pre-incubation temperature (50°C), showing 120% reduction from the amount achievable by the native enzyme. This indicated the crucial role of the hydrophobic residue on helix-loop-helix motif in providing the hydrophobic effect pre-requisite for interfacial activation mechanism. In conclusions, these studies provide better understanding in protein solvent interaction and suggest a suitable parameter in rational design strategy for a better non-aqueous catalysis.